Social cohesion : inclusion and a sense of belonging in Latin America and the Caribbean (ECLAC SantiagoCL, 2007)
Attempts to increase the visibility, identity and depth of social cohesion and to advance its adoption as an important beacon for public policies. Explores several dimensions of social cohesion. Argues in favour of a social cohesion contract for the countries of the region, taking into account the specific features of each country.
Bibliography: p. 157-167